Paparan Media Terhadap Perilaku Berisiko Remaja - Agustin Rahmawati; Siti Istiana; Erna Kusumawati (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2015)
Background: Adolescent life is a life that is crucial for the future of the rest of their lives. Adolescent delinquencecan happen when sociological and psychological needs are not well, so that will bring various pattern of aggressive behavior and tend toward the negative. Aggressive behavior problems tend to be negative and it cannot beseparated from mental problems, and the psychological journey dominant in adolescents is still unstable. Influencescoming from the outside often have an impact that brings them to risky behaviors such as smoking, free sex, anddrugs. Therefore, this study aims to find the effect of media exposure on adolescent risk behavior.Method: The type of research used in this research is a survey research of cross sectional approach. The samplein this research is a part of the population of the students of class XI SMK Sudirman Semarang from June until July2015 which amounted to 39 students. The sampling techniques used are a sampling of saturated.Result: Data obtained by the majority of adolescent who have high-risk behavior as much as 53.8%. Media exposure mostly give positive exposure to 61.5%. Results of the correlation of Chi Square p value = 0.000 (p <0.05). Theinfluence of the incorrect information may negatively impact if not matched with the right information from sourcesthat can be accounted for.Conclusion: There are any significant correlation media exposure with the risky behavior of adolescent.Keywords: risky behavior, adolescents, media exposure